Effect of ultrasonication on the thermal and mechanical properties of plasterboard modified with a microencapsulated phase change material - Vasco-Calle, D; Aranda-Acuna, P; Hermosilla-Dote, E (ELSEVIER, 2026)
This study investigates the effect of ultrasonic dispersion on the thermal and mechanical behavior of gypsum plasterboards incorporating microencapsulated phase change materials (mPCM). Boards containing 10 and 20% w.t. mPCM were prepared by manual mixing and ultrasonic dispersion. Scanning electron microscopy (SEM) confirmed that sonication reduced microcapsule agglomeration and improved distribution within the gypsum matrix. Thermal analysis showed that ultrasonicated samples exhibited higher thermal conductivity and volumetric heat capacity near the PCM transition range (25-29 degrees C). Differential scanning calorimetry (DSC) of sonicated specimens revealed phase-change enthalpies of 24.6 kJ/kg and 28.7 kJ/kg for 10% w.t. and 20% w.t. mPCM, respectively. Despite these thermal improvements, ultrasonic treatment reduced compressive and flexural strength due to cavitation-induced porosity and weakened interfacial bonding. These results demonstrate that ultrasonication enhances thermal performance but compromises mechanical integrity, highlighting the need to optimize mixing conditions for mPCM-gypsum composites in energy-efficient building applications.